Dwarapala at Lakshmi Narayan Temple - Ghosh, Ayan (2023)
Mace-bearing dwarapala at the Lakshmi Narayan Temple wearing the Marathi turban, called pheta or pataka. The dwarapalas at Vishnu temples are modeled on Jaya and Vijaya, the gatekeepers at Vaikuntha, the heavenly abode of Lord Vishnu. The interesting detail is the presence of a small lion at the base.